Plan de negocio para la puesta en marcha de Easy Flavors del Ecuador empresa anexa a Chinito para la producción de fideos instantáneos - Fiallo Romo, Ana María (2010)
Executive summary In chapter I the antecedents of the plan appear: how the idea was born instantaneous to send a new product of Chinese noodles to the market. The general mission is the elaboration of the plan of businesses for the elaboration of the product. The specific objectives are to know the surroundings, to collect information, to elaborate a marketing plan and to analyze the financial viability of the possible business. In chapter II one analyzes the sector and the industry where the business will be developed. The sector of Foods and nonalcoholic Drinks has had a rate of growth of 2.79% between years 2008 and 2009. Within this sector it is the Elaborated Product Industry, which has had a growth of 5.39% between years 2008 and 2009. This information will help us to the development of the plan of businesses and will allow determining if a business opportunity exists. In chapter III an investigation of market was made where a business opportunity appeared, since it counts on the know how’s in addition to the suppliers and distributors. Three interviews to experts were made where knowledge were obtained on the operation of the machine and its capacity of production, which is of, approximately, 5 000 to 8 000 units by every 8 running hours of the same one. Thus also, it could obtain data about the development of the industry and the most influential competitors in the market who are Oriental and Toscana. In addition, three groups of approach were made in where they were interview to clients, who gave information on the consumption habits, preferences of flavors and frequency of purchase. In chapter IV one appears to company EASY FLAVORS OF ECUADOR, with its structure, organizational chart and the operation of each one of the areas that conform it. To the objectives and goals are developed to create and to position The mark in the market, to expand the business at national level, to increase the participation of market, to increase to the sales and the initiation of the operations. Also, the functions of reception of raw material, operations, logistic of exit, marketing and service to the client are analyzed. In I capitulate V appears the marketing plan, where the general mission is described of which it consists of